The Brazilian capital goods industry, 1929-1964 - Leff, Nathaniel H. (Cambridge, Massschusetts: Harvard University Press, 1968)
This is a case study of industrial growth in Brazil, a country whose economy has been able to expand at a relatively high rate despite the well-known barriers of underdevelopment.
Includes bibliographical footnotes.
ne 8/05/2018
Loans
Keywords: Machinery industry; Capital goods; Brazil